PEMBERKASAN SURAT TUGAS DI BIDANG PENGAWASAN INSTANSI PEMERINTAH PUSAT BADAN PENGAWASAN KEUANGAN DAN PEMBANGUNAN PERWAKILAN DAERAH ISTIMEWA YOGYAKARTA - , BANGUN LESTARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This Final Report has a theme of filing of duty letter in Bidang Instansi Pemerintah Pusat, representative of BPKP DIY. According to finance auditing, performance auditing and operational auditing, representative of BPKP DIY produce result of a bundles of duty letter and its completeness. From those process above, the things that should be known are filing, the storage environment, and the finding aids. In arranging of final report, the writer used interview method, participative observation method and research method. Interview method was done by interviewing several expert staffs in BPKP. Participative Observation method was done by observing and doing internship during two months in BPKP. Then operational research method was done by collecting sources material that related with the theme to complete the data. The conclusion of this report, BPKP has filed the duty letter in appropriate system. Therefore, there are several problems in using storage enviroment that are inappropriate with archive rules. Although, those aspects do not bother the finding aids.